Confirmation of Trichophyton Rubrum by Micromorphological and Molecular Techniques and In-Vitro Antifungal Activities of Allicin and Garlic Extracts - Aala, Farzad (2011)
Dermatophytosis caused by a group of pathogenic fungi namely, dermatophytes, is among the most prevalent infectious diseases worldwide. One of the most frequently isolated pathogenic dermatophytes is Trichophyton rubrum. Chemical drugs are widely used in the treatment of dermatomycosis, but can cause various side effects to the patients and drug resistance to the pathogens. Hence, alternative natural compounds should be assessed to solve this problem. Garlic can be considered as a good replacement due to its high level of sulfur compounds (e.g., allicin). Therefore, the main objective of this study was to evaluate allicin and garlic extract against various isolates of T. rubrum. These studies were divided into three parts. The first was to confirm ten different isolates of T. rubrum which were obtained from the Laboratory of Medical Mycology Department in Tehran University of Medical Sciences, Iran by using both conventional and molecular methods. The second part was to evaluate the in vitro antifungal activity of allicin, aqueous garlic extract, ketoconazole and fluconazole and the combination of these azoles drugs with allicin and aqueous garlic extract against these ten isolate of T. rubrum. The third objective was to see the effect of allicin and garlic extract to the ultrastructure of T. rubrum using electron microscope. In this study, colony characterizations of all isolates of T. rubrum are varied and inconclusive. However the molecular study based on Internal Transcribed Spacer, 1 and 4 (ITS1 and 4) revealed that all the different isolates tested with reference from data base in Genbank (BLAST search) showing more than 95% similarity. In vitro antifungal study on the effects of allicin and aqueous garlic extract singly and in combination with ketoconazole and fluconazole against ten clinical isolate of T. rubrum were effective in inhibiting the fungal growth. The results showed that MICs for allicin ranged from 0.78 – 12.5 μg/ml, ketoconazole 0.25 – 8.0 μg/ml and fluconazole 1.0 - 32.0 μg/ml respectively. Combination of allicin or garlic extract with ketoconazole or fluconazole caused the synergistic or additive effect on dermatophytes, which may increase fungicidal effects, decrease toxicity, side effects and drug resistance. Besides, in vitro studies revealed that allicin and aqueous garlic extract alone and in combination with these two azoles drugs, has a good potential as antifungal drug based on the results of MICs (Minimal Inhibitory Concentration) and FICIs (Fractional Inhibitory Concentration Index). The SEM (Scanning Electron Microscopy) micrographs showed that allicin and garlic extract caused shrinkage, rough and irregular- shaped hypha with expanded hyphal tip of T. rubrum. The TEM (Transmission Electron Microscopy) micrographs revealed that allicin and garlic extract caused cell wall thickening, disorganization of cytoplasmic contents and breaking down of cell membrane and cell wall of T. rubrum. SEM and TEM studies proved that allicin and garlic extract possessed antifungal activity by inhibiting the growth of T. rubrum, and can be considered to treat fungal infections. This study showed that although different isolates exhibited different morphological characteristics but molecular analysis proved that they belong to the T. rubrum species. Allicin and garlic extracts were effective in inhibiting dermatophytes growth. In addition, SEM and TEM studies demonstrated that allicin and garlic extract possessed antifungal activity which inhibits the hyphal growth of T. rubrum.